Vibration Control of Corrugated Steel Web Box Girder Bridge with Friction Pendulum Isolation - Wang, Zhen; Hu, Juntao; Jing, Wei; Zhang, Wendong (Salehan Institute of Higher Education, 2024)
In order to investigate the feasibility and applicability of friction pendulum bearings for vibration control of large-span space beam-arch bridges with corrugated steel web box girders, taking the Huian Yellow River Bridge in Guide County, Qinghai Province, China, as an example. A three-dimensional calculation model of the friction pendulum isolation space beam-arch composite bridge with a corrugated steel web was established by MIDAS, the modal analysis was carried out, and the damping effect of the friction pendulum isolation bridge was investigated using the response spectrum and the time history analysis methods; the influence of the design parameters of the friction pendulum isolation on the reduction effect was further analyzed. The results show that the friction pendulum isolation improves the stress conditions of both the girder and the pier and reduces the displacement and acceleration of the pier top, as well as reduces the acceleration of the girder, and the damping ratio is more than 50%. The optimal dynamic coefficient of friction and the radius of curvature for the corrugated steel web composite bridge are 0.04 and 3.0 m, respectively. Friction pendulum isolation has a good seismic absorption effect and provides an effective way for the seismic control of the corrugated steel web composite bridge. Doi: 10.28991/CEJ-2024-010-10-01 Full Text: PDF